Development, Validation, and Application of a Novel Method for the Analysis of Vitamin E Acetate and Other Tocopherols in Aerosol Emissions of E-Cigarettes, or Vaping Products Associated With Lung Injury - Puetz, Andrew; Morel Espinosa, Maria; Watson, Clifford; Blount, Benjamin C.; Valentín-Blasini, Liza (Frontiers in Chemistry, 2021)
E-cigarette, or vaping, product (EVP) use has increased dramatically in the United States over the last four years, particularly in youth and young adults. Little information is available on the chemical contents of these products. Typically, EVPs contain an active ingredient such as nicotine, CBD, or THC dissolved in a suitable solvent that facilitates aerosol generation. One EVP solvent, vitamin E acetate (VEA), has been measured in EVP liquids associated with lung injury. However, no validated analytical methods for measuring VEA in the aerosol from these devices was previously available. Therefore, we developed a high throughput isotope dilution LC-MS/MS method to simultaneously measure VEA and three other related tocopherols in aerosolized EVP samples. The assay was precise, with VEA repeatability ranging from 4.0% to 8.3% and intermediate precision ranging from 2.5% to 6.7%. Similar precision was obtained for the three other tocopherols measured. The LODs for the four analytes ranged from 8.85 x 10-6 to 2.28 x 10-5 µg analyte per mL of aerosol puff volume, and calibration curves were linear (R2 > 0.99). This method was used to analyze aerosol emissions of 147 EVPs associated with EVALI case patients. We detected VEA in 46% of the case-associated EVPs with a range of 1.87 x 10-4 to 74.1 µg per mL of aerosol puff volume and mean of 25.1 µg per mL of aerosol puff volume. Macro-levels of VEA (>0.1% w/w total aerosol particulate matter) were not detected in nicotine or CBD products; conversely 71% of the EVALI associated THC products contained macro-levels of VEA. Trace levels of other tocopherol isoforms were detected at lower rates and concentrations (α-tocopherol: 41% detected, mean 0.095 µg analyte per mL of aerosol puff volume; -tocopherol: 5% detected, mean 0.0193 µg analyte per mL of aerosol puff volume; δ-tocopherol: not detected). Our results indicate that VEA can be efficiently transferred to aerosol by EVALI-associated EVPs vaped using a standardized protocol.